Greater celandine ( Chelidonium majus L.) for COVID‐19: A twenty‐case series - Gardin, Nilo E. (Phytother Res, 2021)
In December 2019, an outbreak of coronavirus disease 2019 (COVID‐19) occurred in Wuhan, China, with a rapid increase in cases worldwide. Until now, among several drugs tested, none demonstrated sufficient efficacy for its etiological treatment. Greater celandine (Chelidonium majus L.) is a well‐known medicinal plant, traditionally indicated for digestive disorders and topically to remove warts. This study, performed at private offices in São Paulo and Aracaju (Brazil), describes 20 consecutive COVID‐19 outpatients treated with greater celandine and their clinical evolution. The patients, aged 14–71 years (median of 41 years), were treated with Chelidonium majus 10% mother tincture, 20–30 drops three times a day for 3–12 days (median of 5 days). Clinical features were assessed during the treatment and at least until 1 week after its end. These cases were considered mild, as most COVID‐19 cases. The symptoms were mainly fever, fatigue, cough, sore throat, coryza, anosmia, ageusia, and headache. Ten patients had comorbidities, such as hypertension, diabetes, and overweight. Complete or almost complete clinical improvement occurred within 1–9 days of treatment (median of 3 days). There were no adverse events. This casuistry, although small, may inspire other researchers to continue investigating Chelidonium majus as a healing treatment for COVID‐19.